2009
DOI: 10.1111/j.1600-9657.2008.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Double ‘pink tooth’ associated with extensive internal root resorption after orthodontic treatment: a case report

Abstract: Advanced internal resorption affecting the crown of teeth may result in the appearance of a 'pink tooth', which, when located in the root canal, can perforate the external root surface. Therapeutically, this condition represents a clinical challenge and normally requires a combined endodontic and surgical focus. Presented herein are cases of double 'pink tooth' which appeared at different times after orthodontic treatment. In the most severe case, upon radiographic examination and computed tomography, the maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 23 publications
0
58
0
2
Order By: Relevance
“…Although most cases are progressive, some cases are transient and arise in traumatised teeth or those that have recently undergone orthodontic or periodontal therapy. 7 For IR to occur, the outermost protective odontoblast layer and the predentin of the canal wall must be damaged, resulting in…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most cases are progressive, some cases are transient and arise in traumatised teeth or those that have recently undergone orthodontic or periodontal therapy. 7 For IR to occur, the outermost protective odontoblast layer and the predentin of the canal wall must be damaged, resulting in…”
Section: Discussionmentioning
confidence: 99%
“…Various aetiological factors have been proposed for the loss of predentin, including trauma, caries and periodontal infections, excessive heat generated during restorative procedures on vital teeth, calcium hydroxide idiopathic dystrophic changes within normal pulp. 3,[7][8][9][10][11][12][13] In a study of 25 teeth with IR, trauma was found to be the most common predisposing factor that was responsible for 45% of cases examined. 14 The suggested aetiologies in the other cases were inflammation as a result of carious lesions (25%) and carious/periodontal lesions (14%).…”
Section: Case Reportmentioning
confidence: 99%
“…The present case demonstrated a successful treatment of a perforating internal root resorption with grey MTA. Successful surgical and nonsurgical treatment of internal resorption in both primary and permanent teeth using MTA has been reported previously in several case reports (5,(9)(10)(11). MTA is biocompatible (12) and has been shown to be effective in repairing furcation perforations (13) and lateral root perforations (14).…”
Section: Discussionmentioning
confidence: 99%
“…Various etiological factors have been proposed for the loss of predentin, including trauma, caries and periodontal infections, excessive heat generated during restorative procedures on vital teeth, calcium hydroxide procedures, idiopathic dystrophic changes within normal pulp, etc. [6][7][8][9][10][11][12] In this case report, the patient's chief complaint was pink color of the crown in #21. The pink discoloration (pink tooth of Mummery, named after the anatomist James Howard Mummery) was due to granulation tissue in growth.…”
Section: Discussionmentioning
confidence: 99%